PERAN ORGANISASI INTERNASIONAL DI WILAYAH PERANG: UPAYA UNICEF DALAM MELINDUNGI HAK-HAK ANAK DI YAMAN - Luerdi Luerdi; Mardiyanti Mardiyanti (Dauliyah Journal of Islamic and International Affairs, 2021)
This paper aims to explain the role of United Nations Children’s Fund (UNICEF)inprotectingandsavingtherightsofchildrenwhobecamevictims in Yemen’s war. Despite the fact that it was an international humanitarian organization under the United Nations’ umbrella created by states, it could operate independently and its behavior was sometimes contrast to states’ interests especially those involved in the conflict. In addition to the research problem, the rareness of study on UNICEF’s behavior in conflict areas especially in Yemen drove this research. The research applied the qualitative methods with a causality analysis. In oder to explain the research problem, the role theory and concept of international organization’s independence fitting the constructivist approach were applied. The research found that the driving factors such as identity, norm and independence created theUNICEF’s role in protecting and saving the children’s rights in Yemen. The paper represents a perspective that non-material factors place the international organization’s role important in globalpolitics